Cover. Issue 4 (15th April 2019) - Luo, Yuqin; Jia, Bei; Yan, Kai; Liu, Siping; Song, Xiaojie; Chen, Mingfa; Jin, Fan; Du, Yang; Wang, Juan; Hong, Yan; Cao, Sha; Li, Dawei; et al.
Abstract : The cover image based on Original Article Pilot study of a novel multi‐functional noninvasive prenatal test on fetus aneuploidy, copy number variation, and single‐gene disorder screening by Yuqin Luo et al., DOI:10.1002/mgg3.597 .